Endobronchial stenting in a rare case of severe necrotic tracheal mucormycosis - T.H. Deepak; Karan Deshmukh; S. Santha Kumar; J. Venugopal (Lung India)
We present a case of tracheal necrosis due to mucormycosis in a young diabetic male. He presented with stridor due to airway obstruction from the necrosed tracheal wall. We used a silicon tracheal stent to maintain airway patency and support the airway. This case highlights the use of tracheal stenting to stabilize the airway in an extremely necrosed and friable trachea, which is not fit for surgical resection due to the involvement of the long segment of the trachea. To the best of our knowledge, the use of stents to stabilize necrosed tracheal walls in cases of mucormycosis has not been reported so far.